Seismic response of submerged floating tunnel under support excitation. (3rd April 2017) - Mirzapour, J.; Shahmardani, M.; Tariverdilo, S.
Abstract: Submerged floating tunnels are an interesting solution for crossing deep water ways. This paper investigates the response of these tunnels considering spatial variation of ground motion excitation. Due to this excitation, the surrounding fluid imposes an additional force on the tunnel. Fluid field is described using two-dimensional (2D) and three-dimensional (3D) velocity potential functions. The spatial variation of ground motion is simulated by the cross spectral density accounting for wave propagation along the tunnel length. The results show that assuming 2D and 3D fluid field have large impact on the displacement pattern and magnitude along tunnel length. It is shown that mode shapes associated with same natural frequency in the 2D and 3D models are completely different and this the main reason behind substantial difference in the seismic response of these models. Effects of spatial variations and change in the stiffness of mooring tethers on the tunnel response are also investigated.